Pengaruh Service Quality dan Online Marketing terhadap Customer Loyalty dan Repurchase Intention, Studi Kasus Brand Eiger - Rafiqi, Farhan; Gunawan, Theresia (Masyarakat Ekonomi Syariah Bogor, 2024)
This research aims to determine the moderating influence of Online Marketing between Service Quality-Customer Loyalty and the mediating influence of Customer Loyalty between Service Quality-Repurchase Intention in the Eiger brand case study. This research is aimed at people who have purchased at least once from the Eiger brand and have seen advertisements on social media. The total sample from the population in this study was 125 respondents who filled out the questionnaire with the help of Google Form. The analysis technique was carried out using Smart PLS with the SEM method. The results of this research prove that Online Marketing does not moderate the influence between Service Quality - Customer Loyalty and Customer Loyalty has a mediating influence between Service Quality - Repurchase Intention.